Management of Colonic Obstruction: A Review - Sawai, Rebecca S. (Clinics in Colon and Rectal Surgery, 2012)
Large bowel obstruction is a common problem with many different causes, the most common being colorectal adenocarcinoma, extracolonic adenocarcinoma, diverticular disease, volvulus, and inflammatory bowel disease. The nature of the obstruction can influence the best management. Historically, treatment of obstruction consisted of surgical removal of the obstruction if possible and decompression of the bowel with an ostomy. Other strategies for managing obstruction have evolved as alternatives to stomas, including primary resection with anastomosis and endoscopic stent placement. The choice of treatment can therefore be tailored to the individual patient with good success.
Keywords: large bowel obstruction; management; colostomy; colectomy; endoscopic stent